2009
DOI: 10.1038/modpathol.2009.114
|View full text |Cite
|
Sign up to set email alerts
|

Widespread activation of the DNA damage response in human pancreatic intraepithelial neoplasia

Abstract: Pancreatic intraepithelial neoplasia (PanIN) lesions are the most common non-invasive precursors of pancreatic adenocarcinoma. We postulated that accumulating DNA damage within the PanIN epithelium activates checkpoint mechanisms. Tissue microarrays were constructed from 81 surgically resected primary pancreatic adenocarcinomas, and an independent set of 58 PanIN lesions (31 PanIN-1, 14 PanIN-2, and 13 PanIN-3). Immunohistochemical labeling was performed using anti- γH2AXSer139, anti-phosphoATMSer1981, anti-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 37 publications
3
33
1
1
Order By: Relevance
“…For example, short term activation of JNK may promote cell survival (21,39), whereas long term activation may lead to increased apoptosis such as through the E3 ubiquitin ligase ITCH that promotes c-Jun degradation (23,40,41). Of interest, USP9x has recently been identified as a tumor suppressor in pancreatic cancer that also exerts it effects though regulation of ITCH expression (24,42), lending support to the notion that ITCH-dependent JNK signaling that leads to apoptosis, a consequence of chronic JNK activation by ongoing DNA damage (25,43), may be one of the cellular functions targeted.…”
Section: Discussionmentioning
confidence: 83%
“…For example, short term activation of JNK may promote cell survival (21,39), whereas long term activation may lead to increased apoptosis such as through the E3 ubiquitin ligase ITCH that promotes c-Jun degradation (23,40,41). Of interest, USP9x has recently been identified as a tumor suppressor in pancreatic cancer that also exerts it effects though regulation of ITCH expression (24,42), lending support to the notion that ITCH-dependent JNK signaling that leads to apoptosis, a consequence of chronic JNK activation by ongoing DNA damage (25,43), may be one of the cellular functions targeted.…”
Section: Discussionmentioning
confidence: 83%
“…The remaining steps were performed using an automated immunostainer (DakoCytomation).Immunolabeled sections were lightly counterstained in with hematoxylin, dehydrated in ethanol, and cleared in xylene. Immunohistochemical labeling of sox17 protein was scored using a previously described histologic score quantifying both the area and intensity of labeling (33). Labeling Intensity was designated as 0–2 for absent, weak, and strong, and the area of labeling was designated as 0–4 for <5%, 5–25%, 26–50%, 51-75, and >76%, respectively (33).…”
Section: Methodsmentioning
confidence: 99%
“…Extensive published evidence has shown that the DDR is activated during development of many tumor types (17). Several reports have shown immunohistochemical evidence that DDR proteins are highly expressed in precancerous lesions but less so in invasive cancers or corresponding normal tissues (4)(5)(6)(7)(8). It is therefore logical to explore these molecules as biomarkers of early cancer development and reasonable to hypothesize that visualization of components of the DDR might provide an excellent means of early cancer detection (9).…”
Section: Discussionmentioning
confidence: 99%
“…Early reports of DDR activation during bladder, colon, breast, skin, and lung cancer development showed that it was accompanied by the activation of signaling proteins downstream of phosphorylated ATM (pATM), including pChk2 and the phosphorylated histone H2A variant H2AX, gH2AX (4,5). DDR activation has since been observed to occur during the development of many other types of cancer including pancreatic (6), ovarian (7), and hepatocellular carcinomas (8). Given the near-ubiquitous nature of DDR activation during oncogenesis, it has been suggested that markers of DNA replication stress and constitutive DDR activation might distinguish neoplastic growth from normal tissues.…”
mentioning
confidence: 99%